Analysis of Differences in Injuries in Padel Players According to Sport-Specific Factors, Level of Physical Activity, Adherence to the Mediterranean Diet, and Psychological Status - Guillermo Rocamora-López; Adrián Mateo-Orcajada (Sports)
The available scientific evidence on padel injuries is scarce and inconclusive. For this reason, the main aim was to analyze the differences in injury incidence in padel according to specific factors of the sport, as well as to the level of physical activity, adherence to the Mediterranean diet, and the psychological state of the players. A sample of 216 padel players (mean age: 30.05 ± 9.50 years old) participated in this study. The participants completed a sociodemographic questionnaire that included padel-specific variables, a sports injury questionnaire, the IPAQ, the MEDAS, and the CPRD. A higher incidence of injuries was observed in players with more experience (p < 0.001), more hours of play (p < 0.001) and at amateur or professional levels (p < 0.001). Mild and moderate injuries were common with mixed or herringbone soles; severe (p = 0.031), muscle, tendon and ligament injuries were common with herringbone soles (p = 0.023). Muscle and ligament injuries occurred more frequently on sand courts (p = 0.037), and with 350–370 g racquets (p = 0.029). Tendon injuries were associated with less mental ability (p = 0.014). There were no significant differences with the Mediterranean diet or level of physical activity. Injury in padel is related to sport-specific factors and psychological state but does not seem to be related to level of physical activity or diet. However, due to the cross-sectional design, causal relationships cannot be established, so future research in this field is needed.